If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=14Y^2-32Y+63
We move all terms to the left:
-(14Y^2-32Y+63)=0
We get rid of parentheses
-14Y^2+32Y-63=0
a = -14; b = 32; c = -63;
Δ = b2-4ac
Δ = 322-4·(-14)·(-63)
Δ = -2504
Delta is less than zero, so there is no solution for the equation
| -2.8=b/6 | | x+1+4x=-9 | | 30=1.6y+15 | | 16x-70=20x | | 6=2(n+2) | | (15/3)*(4+1)=v+5 | | 10x+5=7x+8=8x-1 | | 180=5x+11 | | 52=m+1 | | 0.7(10x+16)=3.4(0.2x+5) | | 6/13=5/13+p | | (15|3)*(4+1)=v+5 | | 25n=125 | | 9+c=14 | | -7-7x+7x=-119 | | d+6=0 | | n-4.2=4.7 | | 4+e=1 | | 7k–8=6 | | 7k–8 = 6 | | -4=2n+2+n | | -4x2-(-2)=^2-3)^3= | | 6u+10=8u+4 | | 1/2x-3/4=1/4x+9 | | 28-7x=3x | | 7/12b=1 | | 5x+12+2x+14=77 | | 50=600f | | 50-9x=77 | | 1.1x+.35=-8.1 | | 8/3z=-9+7 | | -1a-3=-1a-1-2 |